Multifunctional Photosensitizing and Biotinylated Polystyrene Nanofiber Membranes/Composites for Binding of Biologically Active Compounds - Henke, Petr; Dolanský, Jiří; Kubát, Pavel; Mosinger, Jiří (ACS applied materials & interfaces, 2020)
A three-step postprocessing functionalization of pristine electrospun polystyrene nanofiber membranes was used for the preparation of nanostructured biotinylated materials with an externally bonded porphyrin photosensitizer. Subsequently, the material was able to strongly bind biologically active streptavidin derivatives while keeping its photosensitizing and antibacterial properties due to the generation of singlet oxygen under the exclusive control of visible light. The resulting multifunctional materials functionalized by a streptavidin-horseradish peroxidase conjugate as a model bioactive compound preserved its enzymatic activity even in the presence of a porphyrin photosensitizer with some quenching effect on the activity of the photosensitizer. Prolonged kinetics of both singlet oxygen luminescence and singlet oxygen-sensitized delayed fluorescence (SODF) were found after irradiation by visible light. The above results reflected less effective quenching of the porphyrin photosensitizer triplet state by ground state oxygen and indicated hindered oxygen transport (diffusion) due to surface functionalization. We found that SODF could be used as a valuable tool for optimizing photosensitizing efficiency as well as a tool for confirming surface functionalization. Full photosensitizing and enzyme activity could be achieved by a space separation of photosensitizers and enzyme/biomolecules in the nanofiber composites consisting of two layers. The upper layer contained a photosensitizer that generated antibacterial singlet oxygen upon irradiation by light, and the bottom layer retained enzymatic activity for biochemical reactions.
Keywords: fluorescenční barviva; nanokompozity; fluorescenční spektrometrie; Anti-Bacterial Agents; Polystyrenes; delayed fluorescence; nanofibers; singlet oxygen; porfyriny; Porphyrins; Nanocomposites; Streptavidin; Photosensitizing Agents; Fluorescent Dyes; fotosenzibilizující látky; Singlet Oxygen; streptavidin; Spectrometry, Fluorescence; Biotin; Escherichia coli; nanovlákna; membrány umělé; antibakteriální látky; Nanofibers; biotin; Membranes, Artificial; singletový kyslík; polystyreny